Histone acetylation and methylation in the signaling of steroid hormone receptors - Trtková, K.; Bouchal, J.; Kolí r, Z. (Cellular and Molecular Biology, 2007)
Molecular changes associated with malignancy are extremely complex. Early epigenetic events occuring in the common tumor types such as breast or prostate cancer might determine the subsequent genetic changes leading to tumor development and progression. Covalent modifications of histones play a major role as determiners of epigenetic information and are important in the regulation of gene expression. Acetylation generally corelates with transcriptional activation, while methylation can signal either activation or repression. However, little is known about the interplay of different epigenetic events. Steroid hormones regulate many cellular processes through signal transduction pathways that result in a variety of posttranslational modifications. Such modifications can be triggered by steroid hormones in cooperation with coactivators (p160 family proteins, CBP, p300, p/CAF) and/or corepressors (N—Cor, SMRT, TZF). There is still much to learn about their regulation and the molecular and physiological consequences of these modifications.